TaisÄ«r An-Naá¸¥wi al Taâ€™lÄ«mÄ« lÄ« Gará¸ QirÄati An-Nuá¹£Å«á¹£ Al-â€˜Arabiyyah Gair al-MasykÅ«lah - Ardiansyah, Ade Arip; Aziz, Aji Abdul (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2019)
TaisÄ«r An-Naá¸¥wi al Taâ€™lÄ«mÄ« lÄ« Gará¸ QirÄati An-Nuá¹£Å«á¹£ Al-â€˜Arabiyyah Gair al-MasykÅ«lah Ade Arip Ardiansyah, Aji Abdul Aziz Islamic State University of Sunan Gunung Djati Bandung Adearipardiansyah94@gmail.com, aziealmaraby@gmail.com Abstract This research aims at describing the grammatical difficulties faced by the students of the Faculty of Islamic Studies at the University of Muhammadiyah Bandung in reading the unconventional Arabic texts. The attempt by the Faculty of Islamic Studies at the University of Muhammadiyah Bandung is to facilitate the educational method for reading non-Arabic texts. The researcher chose the qualitative approach in the research using the methods of observation and interview for data collection, and the analytical method of analysis of the analysis of Miles and Huberman. The results of the research showed that the grammatical difficulties faced by the students of the Faculty of Islamic Studies at the University of Muhammadiyah Bandung varied from lack of understanding in the concepts of word, compound and sentence, which are essential in the study of grammatical science, and that the facilitation of the educational method carried out by Islamic studies at Muhammadiyah Bandung University, Grammatical and simplistic analysis where the theory of rhetoric and descriptive analysis was used in the analysis of sentence. Keyword: Facilitation of grammar, Reading texts, Arabic. ØªÙŠØ³ÙŠØ± Ø§Ù„Ù†ØÙˆ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠ Ù„ØºØ±Ø¶ Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù†ØµÙˆØµ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ØºÙŠØ± Ø§Ù„Ù…Ø´ÙƒÙˆÙ„Ø© Ø£Ø¯ÙŠ Ø¹Ø§Ø±ÙŠÙ Ø£Ø±Ø¯ÙŠØ§Ù†Ø´Ù‡ØŒ Ø£Ø¬ÙŠØŒ Ø¹Ø¨Ø¯ Ø§Ù„Ø¹Ø²ÙŠØ² Adearipardiansyah94@gmail.com, aziealmaraby@gmail.com Ø§Ù„Ù…Ù„Ø®Øµ Â Ø§Ø³ØªÙ‡Ø¯Ù Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ ÙˆØµÙ Ø§Ù„ØµØ¹ÙˆØ¨Ø§Øª Ø§Ù„Ù†ØÙˆÙŠØ© Ø§Ù„ØªÙŠ ÙˆØ§Ø¬Ù‡Ù‡Ø§ Ø·Ù„Ø¨Ø© ÙƒÙ„ÙŠØ© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¨Ø§Ù„Ø¬Ø§Ù…Ø¹Ø© Ø§Ù„Ù…ØÙ…Ø¯ÙŠØ© Ø¨Ø§Ù†Ø¯ÙˆÙ†Ø¬ ÙÙŠ Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù†ØµÙˆØµ Ø§Ù„Ø¹ Ø±Ø¨ÙŠØ© ØºÙŠØ± Ø§Ù„Ù…Ø´ÙƒÙˆÙ„Ø©ØŒ ÙˆÙˆØµÙ Ø§Ù„Ù…ØØ§ÙˆÙ„Ø© Ø§Ù„ØªÙŠ Ù‚Ø§Ù…Øª Ø¨Ù‡Ø§ ÙƒÙ„ÙŠØ© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¨Ø§Ù„Ø¬Ø§Ù…Ø¹Ø© Ø§Ù„Ù…ØÙ…Ø¯ÙŠØ© Ø¨Ø§Ù†Ø¯ÙˆÙ†Ø¬ ÙÙŠ ØªÙŠØ³ÙŠØ± Ø§Ù„Ù†ØÙˆ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠ Ù„ØºØ±Ø¶ Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù†ØµÙˆØµ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ØºÙŠØ± Ø§Ù„Ù…Ø´ÙƒÙˆÙ„Ø©. ÙˆØ§Ø®ØªØ§Ø± Ø§Ù„Ø¨Ø§ØØ« Ø§Ù„Ù…Ø¯Ø®Ù„ Ø§Ù„Ù†ÙˆØ¹ÙŠ ÙÙŠ Ø§Ù„Ø¨ØØ« Ù…Ø³ØªØ®Ø¯Ù…Ø§ Ø£Ø³Ø§Ù„ÙŠØ¨ Ø§Ù„Ù…Ù„Ø§ØØ¸Ø© ÙˆØ§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø© Ù„Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§ØªØŒ ÙˆØ£Ø³Ù„ÙˆØ¨ Ø§Ù„ØªØÙ„ÙŠÙ„ Ø§Ù„ØªÙØ§Ø¹Ù„ÙŠ Ù„Ù…Ø§Ù„ÙŠØ² ÙˆÙ‡ÙˆØ¨ÙŠØ±Ù…Ø§Ù† Ù„ØªØÙ„ÙŠÙ„Ù‡Ø§. ÙˆØ¯Ù„Øª Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¨ØØ« Ø£Ù† Ø§Ù„ØµØ¹ÙˆØ¨Ø§Øª Ø§Ù„Ù†ØÙˆÙŠØ© Ø§Ù„ÙŠ ÙˆØ§Ø¬Ù‡Ù‡Ø§ Ø·Ù„Ø¨Ø© ÙƒÙ„ÙŠØ© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¨Ø§Ù„Ø¬Ø§Ù…Ø¹Ø© Ø§Ù„Ù…ØÙ…Ø¯ÙŠØ© Ø¨Ø§Ù†Ø¯ÙˆÙ†Ø¬ Ù…ØªÙ†ÙˆØ¹Ø© Ù…ØµØ¯Ø±Ù‡Ø§ Ù…Ù† Ø¹Ø¯Ù… Ø§Ù„ÙÙ‡Ù… ÙÙŠ Ù…ÙØ§Ù‡ÙŠÙ… Ø§Ù„ÙƒÙ„Ù…Ø© ÙˆØ§Ù„Ù…Ø±ÙƒØ¨ ÙˆØ§Ù„Ø¬Ù…Ù„Ø© ÙˆÙ‡ÙŠ Ù…ÙˆØ§Ø¯ Ø£Ø³Ø§Ø³ÙŠØ© ÙÙŠ Ø¯Ø±Ø§Ø³Ø© Ø¹Ù„Ù… Ø§Ù„Ù†ØÙˆØŒ ÙˆØ£Ù† ØªÙŠØ³ÙŠØ± Ø§Ù„Ù†ØÙˆ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠ Ø§Ù„Ø°ÙŠ Ù‚Ø§Ù…Øª Ø¨Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¨Ø§Ù„Ø¬Ø§Ù…Ø¹Ø© Ø§Ù„Ù…ØÙ…Ø¯ÙŠØ© Ø¨Ø§Ù†Ø¯ÙˆÙ†Ø¬ Ø³Ø§Ø±Øª Ø¹Ù„Ù‰ Ø´ÙƒÙ„ Ø¥Ø¹Ø§Ø¯Ø© ØªÙ†Ø³ÙŠÙ‚ Ø§Ù„Ù…ÙˆØ§Ø¯ Ø§Ù„Ù†ØÙˆÙŠØ© ÙˆØªØ¨Ø³ÙŠØ· Ø§Ù„ØªØÙ„ÙŠÙ„ ØÙŠØ« Ø§Ø³ØªØ®Ø¯Ù…Øª Ù†Ø¸Ø±ÙŠØ© Ø¹Ù„Ù… Ø§Ù„Ø¨Ù„Ø§ØºØ© ÙˆØ§Ù„ØªØÙ„ÙŠÙ„ Ø§Ù„ÙˆØµÙÙŠ ÙÙŠ ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¬Ù…Ù„Ø©. Ø§Ù„ÙƒÙ„Ù…Ø© Ø§Ù„Ø±Ø¦ÙŠØ³ÙŠØ©: ØªÙŠØ³ÙŠØ± Ø§Ù„Ù†ØÙˆØŒ Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù†ØµÙˆØµØŒ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©.